Post-radiation epithelioid angiosarcoma of the bladder: A true pathological diagnostic challenge - Filosa Alessandra; Collina Guido (Elsevier, 2020)
Primary angiosarcomas of the bladder are rare tumors of middle-aged and elderly men that typically present with advanced disease. The association of angiosarcoma with therapeutic radiation has been described. Microscopically it consists of atypical anastomosing vascular channels. It is not uncommon for this tumor to dedifferentiate and form sheets of primitive cells, spindle cells and epithelioid cells. Awareness of the histopathologic spectrum of angiosarcoma is important for the correct diagnosis. Immunohistochemical positivity for vascular markers, including CD31, CD34, ERG, and factor VIII is essential. We report a case of bladder angiosarcoma arisen after pelvic irradiation for prostate carcinoma and diagnosed after a bone marrow trephine biopsy.